Knowledge and learning at work - Ash, Eve.; Quarry, Peter; Safari eBooks ([S.l.] : Seven Dimensions, 2014)
"We are continuing to evolve and become more proactive about learning, knowledge and how to manage these factors in a virtual world. These seven video chapters cover key issues for many businesses."--Resource description page.
Title from resource description page (viewed Apr. 8, 2014).
Presenter, Peter Quarry.
Keywords: Knowledge management; Intellectual capital; Knowledge workers; Electronic books